Applying biofluid metabonomic techniques to analyze the combined subchronic toxicity of propoxur and permethrin in rats. (December 2012) - Liang, Yu-Jie; Wang, Hui-Ping; Long, Ding-Xin; Wu, Yi-Jun
Background: NMR combined with pattern recognition was recently introduced as a new technique for rapid xenobiotic toxicity evaluation. In this article, metabolic changes in the biofluid of rats after 90-day oral treatment with propoxur, permethrin and a combination of these two pesticides were investigated.Results: Propoxur dosing induced increased urinary taurine, creatinine and glucose, whereas urinary lactate and acetate were increased in the highest permethrin dose group. Urinary acetate, alanine, lactate and trimethylamine levels were increased in the mixture group, accompanied by decreased urinary tricarboxylic acid cycle intermediates. In addition, the highest dose of the mixture displayed raised 3-D -hydroxybutyrate, acetate and lactate levels in the serum sample.Conclusion: Chronic exposure to a combination of propoxur and permethrin may induce hepatotoxicity and nephrotoxicity. An increase in acetate, alanine and formate in the urine could be a potentially sensitive biomarker of the chronic, combined effects of permethrin and propoxur.